Hadis Kuraib Dalam Konsep Rukyatul Hilal - M. Muslih Husein (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Hisab and rukyat are methods used to determine the beginning of a new month.This study shows several findings. First, there is a correlation between the Kuraib tradition and the differences in determining the beginning of Ramadan, Shawwal, and Dhul-Hijjah in Indonesia. The Ministry of Religious Affairs of the Republic of Indonesia has declared Indonesia as a single jurisdiction (wilayatul hukmi). Second, the success of rukyat al-hilal in one region applies to other regions of the earth. It is important to note that the first visibility of the new moon does not cover the entire surface of the earth on the same day, but is divided into two parts: (1) the western part that can see the new moon, and (2) the eastern part that cannot see the new moon.